Is There a "Chinese School" of IR? - Nele Noesselt (German Institute of Global and Area Studies (GIGA), 2012)
Research on Chinese International Relations (IR) theory has produced a variety of discourses, including post-positivist analyses, contributions by area specialists and China watchers, and articles by Chinese IR scholars. These strands, however, hardly overlap or communicate with each other. To close the gap between the self-reflection of the core (Western IR) (Waever/Tickner 2009: 3) and the periphery's revolt against [Western] IR paradigms (ibid.), it is necessary to view China (and other non-Western regions) as more than simply a playground for theory testing. This paper thus goes beyond the metatheoretical debate about the possibility of non-Western IR. It argues that even though the IR debates in China are heavily influenced by the trends of Western IR Studies, the claim regarding the establishment of a Chinese school of IR is not a hollow slogan. Indigenous frameworks are already under construction.
Keywords: 300; China; international relations (IR) theory; post-positivism; tianxia; world order; China; Weltwirtschaftsordnung; Internationale Beziehungen; Politikwissenschaft